Impact of sports interventions on aggressive behavior among adolescents: a systematic review and meta-analysis - Wang, Hongliang; Chen, Shiwei; Gou, Wenling; Han, Xue (Frontiers in Psychology, 2025)
IntroductionAggression in adolescents adversely affects developmental and mental health outcomes. Sports participation has been proposed as a potential way to reduce aggression by improving self-control and social skills; however, the evidence remains inconsistent. Therefore, this study systematically evaluated the effects of sports interventions on aggression, hostility, and anger in adolescents.MethodsA systematic literature search was performed in PubMed, Embase, the Web of Science, the Cochrane Library, and EBSCOhost-SPORTDiscus up to 15 July 2025. Meta-analysis was conducted to calculate standardized mean differences (SMDs) for aggression outcomes using a random-effects model. Subgroup analyses and sensitivity tests were performed to explore the sources of heterogeneity.ResultsA total of 11 studies with 1,811 participants were included. For aggression, no significant overall effect of sports interventions was found (I2 = 86%, Hedges’ g = 0.46, 95% CI − 0.24 to 1.16). Subgroup analysis by sport type also showed no significant effects. For hostility, a significant reduction was observed (I2 = 0.0%, Hedges’ g = 0.29, 95% CI 0.13 to 0.45). For anger, no significant overall effect was found (I2 = 77.2%, Hedges’ g = 0.32, 95% CI − 0.19 to 0.84). Subgroup analysis showed a significant effect for non-contact sports (I2 = 9.5%, Hedges’ g = 0.52, 95% CI 0.18 to 0.86), but no significant effect was observed for contact sports.ConclusionSports interventions may reduce hostility but have no significant impact on aggression and anger in adolescents. Non-contact sports showed a significant effect in reducing anger. Meanwhile, no significant effects were found for aggression or anger in contact sports, suggesting that while sports interventions could help mitigate hostility, their effectiveness in addressing aggression and anger requires further investigation. Further longitudinal studies are needed to confirm long-term effects and clarify the psychological mechanisms, such as self-control and social skills, through which sports may influence aggression-related outcomes.